ANALYSIS OF PERFORMANCE DETERMINING FACTORS EMPLOYEES THROUGH WORK PRODUCTIVITY AS INTERVENING VARIABLES - Andriani, Yessy; Komaludin, Ade; Hanapia, Asep Yusup (Jurnal Ekonomi Manajemen, 2023)
The main objective of this study is to determine the effect of human capital, organizational commitment, spiritual intelligence, and intellectual intelligence on performance as measured by work productivity partially or simultaneously. This study's PLS-SEM analysis led to the following conclusions: (1) There is a considerable positive influence of organizational commitment, human capital, and spiritual intelligence on employee work productivity, whereas intellectual intelligence has a negative and negligible effect. (2) While intellectual intelligence has a negative and minor impact on employee performance, human capital, organizational dedication, and spiritual intelligence all have a considerable beneficial impact. (3) There is a sizable positive relationship between employee performance and job productivity. (4) Work productivity as an intervening variable for workers has a large positive relationship with human capital, organizational commitment, and spiritual intelligence, but a negative and negligible relationship with intellectual intelligence. The study's novel conclusion is that both directly and indirectly, the discovery of spiritual intelligence positively affects performance through job productivity.